2016
DOI: 10.1002/jso.24533
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer in the young: An advanced disease with poor prognostic features

Abstract: Early-onset gastric cancer demonstrates advanced stage of disease, and a high incidence of poorly-differentiated and signet-cell type carcinoma. Overall survival is poor with no added benefit to surgical intervention in advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
3
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 28 publications
6
64
3
12
Order By: Relevance
“…Therefore, the challenge of early diagnosis and treatment of GC also extends to young patients. Recent data have revealed that young adults gastric cancer (YAGC) accounts for 2-8% of all cancers 5,6 . Besides the obvious social impact, YAGC calls for more and more interest due to the growing importance attached to the genetic causes of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the challenge of early diagnosis and treatment of GC also extends to young patients. Recent data have revealed that young adults gastric cancer (YAGC) accounts for 2-8% of all cancers 5,6 . Besides the obvious social impact, YAGC calls for more and more interest due to the growing importance attached to the genetic causes of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The cut-off value of age to define YAGC has been predictably controversial. Frequently, it has been defined between the limits of 40 and 50 years, without a clear reason 5,6,10,11,17,[19][20][21][22] . Takatsu et al 5 These distinct cut-off values may also reflect different national policies for defining and collecting data on cancer cases in adolescents and young adults, including tumor types other than GC 19,23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed similar results, Yin et al [24] reported a slight increase of mortality for gastric cancer in this age group. This increase in mortality can be due to the fact that young patients tend to present themselves in advanced stages associated with pathological characteristics of seal ring carcinoma and poorly differentiated carcinoma; these being related to wrong prognostic factors [25].…”
Section: Mortality In Young Adult Menmentioning
confidence: 99%
“…In order to improve the clinical management of such malignancy, studies on exploiting novel pathogenic variations in CDH1 and new susceptibility genes for HDGC in Chinese population are required to further elucidate the molecular mechanism of HDGC. Given that early-onset gastric cancers showed advanced stage of disease with high proportion of poorly differentiated carcinomas (14), and that early age of diagnosis potentially indicate presence of familial and hereditary cancer which may be attributable to genetic factors, therefore, investigating on such group of cancer patients may assist to identify susceptibility genes to gastric cancer.…”
Section: Introductionmentioning
confidence: 99%